THE POSITION OF QANUN 6 OF 2014 ON JINAYAT LAW TOWARD ACT 11 OF 2012 ON JUVENILE CRIMINAL JUSTICE SYSTEM RELATED TO CHILD CRIMINAL PUNISHMENT - Iman, Rifqi Qowiyul (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2021)
This paper aims to describe the differences andÂ the position of the legal rules for juvenile crimes between Qanun 6 of 2014 and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Â This research is descriptive qualitative research. The results show that Qanun Number 6 of 2014 also regulates criminal sanctions for children, which are normatively regulated in Law Number 11 of 2012. In addition, Qanun, as Aceh Islamic criminal law legalizes canning punishmentÂ for children, as well as the double-track system adopted by The Law of Juvenile Criminal Justice System is not explicitly accommodated in Qanun. Qanun at the level of a Regional Regulation is part of the hierarchy of laws and regulations that should be in line with what generally applies at the national level. Law Number 11 of 2006 is being the basis of the authority to make Qanun, as long as there is no court decision invalidates it, Qanun Number 6 of 2014, which is a derivative of Law Number 11 of 2006, can be declared as